ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2012-2016 - admin, syarifah nike erla ningsih B2092142009 (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2019)
ABSTRACTThis research aims to determine the factors that affect audit delay in manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. The factors tested in this study are solvability, profitability, liquidity, auditor opinion, firm size, and PAF quality as independent variables and audit delay as the dependent variable. This research is a comparative research with an ex-post pact approach, with a purposive sampling method. The research samples were 29 manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016, so that the research data analyzed amounted to 145 companies. The analytical method used were descriptive analysis, classical assumption test, and multiple linear regression. The results showed that, the auditor’s opinion and company size had a significant effect on audit delay, while the liquidity, profitability, quality org PAF, solvability did no significantly affect audit delay, and simultaneously firm size auditor’s opinion, PAF quality, solvability, liquidity, profitability affected audit delay.Keywords : audit delay, auditor’s opinion, PAF quality, company size, solvability, profitability, and liquidity.